(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
There are a number of factors that might cause fresh water bodies in tropical nations to beaffected by pollution and nutrient influx, heavy metal and elemental precipitation, and continual silt inflow.Anybody of water‘s physicochemical properties is critical. These features are very variable in lentic bodiesof water, which have lower water levels in the summer and higher ones during rainstorms. A water body’soverall health may be gauged by the algal assemblage’s response to these unfavourable conditions. Overthe course of a year, researchers tracked a variety of physico-chemical parameters and algae diversity.